Synthesis of holey graphene networks functionalized with p-phenylene diamine monomers for superior performance flexible solid-state supercapacitors. (10th October 2019) - Du, Pengcheng; Dong, Yuman; Kang, Hongxing; Wang, Qi; Niu, Jingye
Abstract: p-Phenylene diamine (PPD) was selected as functional monomer to modify the holey graphene networks (rHGO-PPD) by a facile one-step hydrothermal method. rHGO-PPD was employed as promising active electrode materials to apply in supercapacitors (SCs), which exhibited excellent electrochemical performance, including high specific capacitance (375.5 F/g at current density of 0.5 A/g), excellent rate capability and good cycling stability due to the contribute of pseudocapacitive behavior of PPD. For further pursuit of great value in the practical application, the rHGO-PPD was used to fabricate symmetric SCs and flexible solid-state SCs (FSSCs). The FSSCs possessed high specific capacitance of 332.4 F/g, maintained good cycling stability of 74% of its initial capacitance up to 5000 charge-discharge cycles. In addition, FSSCs also exhibited extraordinary mechanical flexibility, and also maintained excellent stability even in a harsh environment. Remarkably, the FSSCs showed excellent long-term storage stability, and the capacitance kept about 88% after ten weeks of storage. Therefore, the FSSCs based on rHGO-PPD electrode material display promising application in flexible energy-storage devices. Graphical abstract: Image 1 Highlights: rHGO-PPD exhibits excellent specific capacitance of 375.5 F/g. FSSCs based on rHGO-PPD possess high specific capacitance of 332.4 F/g and good cycle stability. FSSCs exhibits extraordinary mechanical flexibility even in a harsh environment. It maintains excellent long-term storage stability of 88% retention after ten weeks of storage.